Dealing with angry customers (Santa Monica, Calif. : Salenger Film, 1982)
It shows how to deal with angry customers by first dealing with the person's feelings and then by finding a solution to the customer's problem
Copy also available in DVD format
Copy available in DVD format
Keywords: Customer services; Consumer complaints